Variasi Intensitas Kata Sifat Dalam Bahasa Madura - Harrifah Mardatillah; Ika Nurhayani; Hamamah Hamamah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The variations of Madurese intensifying adjectives were investigated in this study. This qualitative study uses a questionnaire as the main instrument to know the intensifying adjectives used by the participants. The participants were asked to translate some sentences from Indonesian to Madurese based on their daily conversations. The participants are native Madurese speakers aged between 15-60 years. The study revealed that there were 28 variations of intensifying adjectives in Madurese which consist of 17 variations of quality level, 3 variations using a determiner before an adjective, 4 variations using a determiner after adjective, 9 variations using a determiner and suffix, and 1 variation using a confix. In the comparative level, it can be divided into equative, comparative, and superlative. There are 5 variations from a comparison of the equivalent level in Madurese, while in the comparative level only one variation is done, it is the addition of lebbi ... deri ..., and the superlative level found 5 variations in the intensity of adjectives.